2018
DOI: 10.1016/j.ophtha.2018.05.001
|View full text |Cite
|
Sign up to set email alerts
|

A Dosing Study of Bevacizumab for Retinopathy of Prematurity

Abstract: Retinal structural outcomes are very good after low-dose bevacizumab treatment for ROP, although many eyes received additional treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
78
2
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 103 publications
(86 citation statements)
references
References 27 publications
3
78
2
3
Order By: Relevance
“…Another study of 24 eyes with type 1 prethreshold ROP who received 0.1 mg of intravitreal ranibizumab showed regression of disease in all cases without any recurrence of disease or need for treatment at 54 weeks post-menstrual age 37. These findings coincide with dose de-escalation studies of bevacizumab for ROP, which found that dosing between 2.5% and 20% of the adult dose of bevacizumab may be effective in controlling acute ROP though these dose levels may lead to higher rates of recurrence 40,41…”
Section: Optimal Dose Of Ranibizumabsupporting
confidence: 81%
“…Another study of 24 eyes with type 1 prethreshold ROP who received 0.1 mg of intravitreal ranibizumab showed regression of disease in all cases without any recurrence of disease or need for treatment at 54 weeks post-menstrual age 37. These findings coincide with dose de-escalation studies of bevacizumab for ROP, which found that dosing between 2.5% and 20% of the adult dose of bevacizumab may be effective in controlling acute ROP though these dose levels may lead to higher rates of recurrence 40,41…”
Section: Optimal Dose Of Ranibizumabsupporting
confidence: 81%
“…Wallace et al showed that a dose of bevacizumab as low as 0.031mg may be effective [30]. However, the author also reported that more patients receiving low-dose bevacizumab required additional treatment [31]. In addition, different anti-VEGF agents, for example ranibizumab and aflibercept, have demonstrated efficacy in treatment of type 1 ROP [27, 32].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that a dosage of bevacizumab as low as 0.031 mg can be effective in ROP treatment, and further investigation into the optimal dosage is required, as are new assessments of the effectiveness and systemic safety of the treatment. [15] IVB monotheraphy might be a feasible option for the achievement of ROP regression with good anatomical outcomes. However, several cases of delayed reactivation have been reported with this method—sometimes as long as 3 years post-IVB treatment.…”
mentioning
confidence: 99%